2011
DOI: 10.3130/jaabe.10.203
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance of Nonstructural Brick Walls Used in Indonesian R/C Buildings

Abstract: This paper describes the effects of nonstructural brick walls on the seismic performance of reinforced concrete (R/C) buildings. Experimental and analytical studies were conducted on two buildings: one of which collapsed and the other suffered moderate damage due to the 2007 Sumatra, Indonesia earthquakes. A brick wall was extracted from the moderately damaged building and transported to Japan from Indonesia to experimentally evaluate its seismic performance. Two R/C one-bay frame specimens were constructed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 1 publication
0
19
0
3
Order By: Relevance
“…They concluded that the masonry infill increased the stiffness and strength of the global structures despite increases in the inertia forces. The authors also performed cyclic loading tests on typical Indonesian R/C frames with brick masonry infill, finding that the masonry infill increased the overall stiffness and strength but decreased the ductility. In contrast, Zovkic et al reported that the deformation capacities of ductile R/C frames designed according to Eurocode 8 were not decreased by the presence of brittle infill.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…They concluded that the masonry infill increased the stiffness and strength of the global structures despite increases in the inertia forces. The authors also performed cyclic loading tests on typical Indonesian R/C frames with brick masonry infill, finding that the masonry infill increased the overall stiffness and strength but decreased the ductility. In contrast, Zovkic et al reported that the deformation capacities of ductile R/C frames designed according to Eurocode 8 were not decreased by the presence of brittle infill.…”
Section: Introductionmentioning
confidence: 91%
“…The specimens represented a partial frame of the moderately damaged building (Figure (c)). The following experimental program and results have been partially reported in Maidiawati et al with the exception of two specimens with infill consisting of scaled bricks.…”
Section: Experimental Study On Infill Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption indicates that a strain profile along the strut width is similar to the profile of the quotient obtained by (d i (y) À d c (y))/l s (y) as shown in the close-up in Figure 1b. Thus, the averaged stress, f m of strut is represented by Equations (1) and (2) given an ideal linear relationship between stress and strain as follows:…”
Section: Rc Column-masonry Infill Interaction Model 21 Strut Replacementioning
confidence: 99%
“…Pemodelan dinding bata diverifikasi dengan hasil pengujian model struktur rangka beton bertulang tanpa dinding (bare frame) dan struktur rangka diisi dengan dinding bata (infilled frame) yang dilakukan oleh penulis (Maidiawati et al 2011). Model struktur rangka dan dinding bata, seperti dintunjukkan dalam Gambar 6 mewakili bentuk struktur bangunan Indonesia, diuji dengan beban siklik statik seperti ditunjukkan pada skema pengujian dalam Gambar 7.…”
Section: Pengujian Struktur Untuk Verifikasi Model Dindingunclassified